A Comprehensive Brownian Dynamics Approach for the Determination of Non-ideality Parameters from Analytical Ultracentrifugation - Uttinger, Maximilian; Wawra, Simon; Guckeisen, Tobias; Walter, Johannes; Baer, Andreas; Thajudeen, Thaseem; Sherwood, Peter J.; Smith, Ana-Suncana; Wagemans, Anja M.; Stafford, Walter F.; Peukert, Wolfgang (Langmuir, 2019)
Brownian dynamics (BD) has been applied as a comprehensive tool to model sedimentation and diffusion of nanoparticles in analytical ultracentrifugation (AUC) experiments. In this article, we extend the BD algorithm by considering space-dependent diffusion and solvent compressibility. With this, the changes in the sedimentation and diffusion coefficient from altered solvent properties at increased pressures are accurately taken into account. Moreover, it is demonstrated how the concept of space-dependent diffusion is employed to describe concentration-dependent sedimentation and diffusion coefficients, in particular, through the Gralen coefficient and the second virial coefficient. The influence of thermodynamic nonideality on diffusional properties can be accurately simulated and agree with well-known evaluation tools. BD simulations for sedimentation equilibrium and sedimentation velocity (SV) AUC experiments including effects of hydrodynamic and thermodynamic nonideality are validated by global evaluation in SEDANAL. The interplay of solvent compressibility and retrieved nonideality parameters can be studied utilizing BD. Finally, the second virial coefficient is determined for lysozyme from SV AUC experiments and BD simulations and compared to membrane osmometry. These results are in line with DLVO theory. In summary, BD simulations are established for the validation of nonideal sedimentation in AUC providing a sound basis for the evaluation of complex interactions even in polydisperse systems.
CRIS-Team Scopus Importer:2019-09-17
Keywords: Brownian movement; Centrifugation; Compressibility; Hydrophobicity; Petroleum reservoir evaluation; Sedimentation; Solvents; Analytical ultracentrifugation; Concentration-dependent; Polydisperse systems; Second virial coefficients; Sedimentation equilibrium; Sedimentation velocities; Solvent compressibility; Thermodynamic non idealities; Diffusion

A multiwavelength emission detector for analytical ultracentrifugation - Wawra, Simon; Onishchukov, Georgy; Maranska, Maria; Eigler, Siegfried; Walter, Johannes; Peukert, Wolfgang (Nanoscale Advances, 2019)

Brownian dynamics simulations of analytical ultracentrifugation experiments exhibiting hydrodynamic and thermodynamic non-ideality - Uttinger, Maximilian; Walter, Johannes; Thajudeen, Thaseem; Wawra, Simon; Peukert, Wolfgang (Nanoscale, 2017)

Determination of 2D Particle Size Distributions in Plasmonic Nanoparticle Colloids via Analytical Ultracentrifugation: Application to Gold Bipyramids. - Frank, Uwe; Drobek, Dominik; Sánchez-Iglesias, Ana; Wawra, Simon; Nees, Nico; Walter, Johannes; Pflug, Lukas; Apeleo Zubiri, Benjamin; Spiecker, Erdmann; Liz-Marzan, Luis M.; Peukert, Wolfgang (ACS nano, 2023)
Multidimensional particle properties determine the product properties in numerous advanced applications. Accurate and statistically meaningful measurements of complex particles and their multidimensional distributions are highly challenging but strongly needed. 2D particle size distributions of plasmonic nanoparticles of complex regular shape can be obtained from analytical ultracentrifugation experiments via the optical back coupling method. A workflow for the calculation of frictional properties of arbitrarily shaped nanoparticles was developed based on bead shell models and applied to gold bipyramids with a pentagonal cross-section. The obtained 2D particle length-diameter distributions and the reduced cumulative 1D length and diameter distributions were compared to transmission electron microscopy measurements. While we find very good agreement for most measurements, the obtained length and diameter distributions were shifted by a few nanometers for some samples. Transmission electron microscopy, energy-dispersive X-ray spectroscopy, electron tomography, and finite element modeling indicate that the shift originated from a slight mismatch between the assumed shape of the simulated perfect bipyramids and the real particle shape and composition due to the presence of silver in the particles. This study demonstrates the feasibility of the applied techniques for complex shape analysis of nanoparticle ensembles with unmatched particle count numbers.
Keywords: analytical ultracentrifugation; bead modeling; electron tomography; extinction cross section; gold bipyramids; optical back coupling; particle shape distribution

Determination of the two-dimensional distributions of gold nanorods by multiwavelength analytical ultracentrifugation - Wawra, Simon; Pflug, Lukas; Thajudeen, Thaseem; Kryschi, Carola; Stingl, Michael; Peukert, Wolfgang (Nature Communications, 2018)
Properties of nanoparticles are influenced by various parameters like size, shape or composition. Comprehensive high throughput characterization techniques are urgently needed to improve synthesis, scale up to production and make way for new applications of multidimensional particulate systems. In this study, we present a method for measuring two-dimensional size distributions of plasmonic nanorods in a single experiment. Analytical ultracentrifuge equipped with a multiwavelength extinction detector is used to record the optical and sedimentation properties of gold nanorods simultaneously. A combination of sedimentation and extinction properties, both depending on diameter and length of the dispersed nanorods, is used to measure two-dimensional distributions of gold nanorod samples. The length, diameter, aspect ratio, volume, surface and cross-sectional distributions can be readily obtained from these results. As the technique can be extended to other non-spherical plasmonic particles and can be used for determining relative amounts of particles of different shapes it provides complete and quantitative insights into particulate systems.
EAM Import::2019-03-13

Development of an advanced multiwavelength emission detector for the analytical ultracentrifuge - Lautenbach, Vanessa; Onishchukov, Georgy; Wawra, Simon; Frank, Uwe; Hartmann, Lukas; Peukert, Wolfgang; Walter, Johannes (Nanoscale Advances, 2024)
An advanced design of the analytical ultracentrifuge with multiwavelength emission detection (MWE-AUC) is presented which offers outstanding performance concerning the spectral resolution and range flexibility as well as the quality of the data acquired. The excitation by a 520 nm laser is complemented with a 405 nm laser. An external spectrograph with three switchable tunable gratings permits optimisation of the spectral resolution in an order of magnitude range while keeping the spectral region broad. The new system design leads also to a significant reduction of systematic signal noise and allows the assessment and control of inner filter effects. Details regarding the very large signal dynamic range are presented, an important aspect when studying samples in a broad concentration range of up to five orders of magnitude. Our system is validated by complementary studies on two biological systems, fluorescent BSA and GFP, using the commercial Optima AUC with absorbance detection for comparison. Finally, we demonstrate the capabilities of our second generation MWE-AUC with respect to multiwavelength characterisation of gold nanoclusters, which exhibit specific fluorescence depending on their structure. Overall, this work depicts an important stepping stone for the concept of multiwavelength emission detection in AUC. The MWE-AUC developed, being to our knowledge the first and sole one of its kind, has reached the development level suitable for the future in-depth studies of size-, shape- and composition-dependent emission properties of colloids.
CRIS-Team Scopus Importer:2024-03-22

Estimation of bivariate probability distributions of nanoparticle characteristics, based on univariate measurements - Furat, Orkun; Frank, Uwe; Weber, Matthias; Wawra, Simon; Peukert, Wolfgang; Schmidt, Volker (Inverse Problems in Science and Engineering, 2020)
The properties of complex particle systems typically depend on multivariate distributions of particle properties, like size and shape characteristics. Multidimensional particle property distributions can be a powerful tool to describe these systems. However, only few techniques exist which are able to simultaneously measure more than one property of individual particles in fast and efficient ways. It is shown how two-dimensional property spaces can be constructed by the combination of two univariate measurements to obtain bivariate particle size distributions. The proposed method is a general approach, which can be applied to a wide spectrum of particle systems and measurement devices. In this paper, the results of a case study are presented, which allow the estimation of bivariate distributions of length and diameter of nanorods, solely using univariate distributions of their particle mass and extinction-weighted sedimentation coefficient distributions. These quantities contain joint information about the particle lengths and diameters, which is used for the reconstruction. The method is validated in a simulation study in which the bivariate distribution to be reconstructed and the reconstruction parameters are varied. In addition, regularization techniques are introduced to reduce methodical errors. This approach can be transferred to other particle systems and measurement techniques, for which functional relationships between particle properties and measured quantities are well describe
Keywords: particle size distributions; reconstruction; inverse problem; Multidimensional characterization; copulas

Ionomer and protein size analysis by analytical ultracentrifugation and electrospray scanning mobility particle sizer - Wawra, Simon; Thoma, Martin; Walter, Johannes; Lübbert, Christian; Thajudeen, Thaseem; Damm, Cornelia; Peukert, Wolfgang (European Biophysics Journal, 2018)
Keywords: Analytical ultracentrifugation; Scanning mobility particle sizer; Combined analysis; Multiwavelength detector

Measurement of length distribution of beta-lactoglobulin fibrils by multiwavelength analytical ultracentrifugation - Uttinger, Maximilian; Heyn, Timon R.; Jandt, Uwe; Wawra, Simon; Winzer, Bettina; Keppler, Julia K.; Peukert, Wolfgang (European Biophysics Journal, 2020)
The whey protein beta-lactoglobulin is the building block of amyloid fibrils which exhibit a great potential in various applications. These include stabilization of gels or emulsions. During biotechnological processing, high shear forces lead to fragmentation of fibrils and therefore to smaller fibril lengths. To provide insight into such processes, pure straight amyloid fibril dispersions (prepared at pH 2) were produced and sheared using the rotor stator setup of an Ultra Turrax. In the first part of this work, the sedimentation properties of fragmented amyloid fibrils sheared at different stress levels were analyzed with mulitwavelength analytical ultracentrifugation (AUC). Sedimentation data analysis was carried out with the boundary condition that fragmented fibrils were of cylindrical shape, for which frictional properties are known. These results were compared with complementary atomic force microscopy (AFM) measurements. We demonstrate how the sedimentation coefficient distribution from AUC experiments is influenced by the underlying length and diameter distribution of amyloid fibrils. In the second part of this work, we show how to correlate the fibril size reduction kinetics with the applied rotor revolution and the resulting energy density, respectively, using modal values of the sedimentation coefficients obtained from AUC. Remarkably, the determined scaling laws for the size reduction are in agreement with the results for other material systems, such as emulsification processes or the size reduction of graphene oxide sheets.
CRIS-Team Scopus Importer:2020-02-11
Keywords: Amyloid fibrils; Analytical ultracentrifugation; Atomic force microscopy; Beta-lactoglobulin; Sedimentation analysis

Multidimensional Fractionation of Particles - Frank, Uwe; Dienstbier, Jana; Tischer, Florentin; Wawra, Simon; Gromotka, Lukas; Walter, Johannes; Liers-Bergmann, Frauke; Peukert, Wolfgang (Separations, 2023)
The increasing complexity in particle science and technology requires the ability to deal with multidimensional property distributions. We present the theoretical background for multidimensional fractionations by transferring the concepts known from one dimensional to higher dimensional separations. Particles in fluids are separated by acting forces or velocities, which are commonly induces by external fields, e.g., gravitational, centrifugal or electro-magnetic fields. In addition, short-range force fields induced by particle interactions can be employed for fractionation. In this special case, nanoparticle chromatography is a recent example. The framework for handling and characterizing multidimensional separation processes acting on multidimensional particle size distributions is presented. Illustrative examples for technical realizations are given for shape-selective separation in a hydrocyclone and for density-selective separation in a disc separator.
Keywords: multidimensional separation; two-dimensional property distribution; size; shape; composition

Multidimensional Particle Size Distributions and Their Application to Nonspherical Particle Systems in Two Dimensions - Frank, Uwe; Wawra, Simon; Pflug, Lukas; Peukert, Wolfgang (Particle & Particle Systems Characterization, 2019)
Particle science and technology evolve toward ever increasing complexity with respect to the multidimensional particle properties of size, shape, surface, internal structure, and composition. In this study, the theoretical background is elaborated for multidimensional particle size distributions (PSDs) by transferring the concepts known from 1D size distributions to anisotropic particles comprising at least two different length dimensions, e.g., nanorods and platelets. After introducing 2D PSDs, the calculation of differently weighted probability density functions including their interconversion is presented. This is necessary in order to compare data resulting from different measurement techniques which probe different physical properties and thus provide differently weighted PSDs. In addition, it is shown how 1D distributions with reduced content of information can be deduced from 2D PSDs. As a proof-of-concept and for illustration purposes, this approach is applied to a 2D Gaussian size distribution. Furthermore, a generalized scheme is suggested which outlines the conversion of number, surface, and volume weighted densities within the 2D space. The application of these methods to the more general n-dimensional case is straightforward.
CRIS-Team Scopus Importer:2019-06-04
Keywords: 2D distributions; multidimensional characterization; particle size distributions; particle technology

New Prospects for Particle Characterization Using Analytical Centrifugation with Sector-Shaped Centerpieces - Uttinger, Maximilian; Boldt, Sebastian; Wawra, Simon; Freiwald, Tobias; Damm, Cornelia; Walter, Johannes; Lerche, Dietmar; Peukert, Wolfgang (Particle & Particle Systems Characterization, 2020)
Analytical centrifugation (AC) has recently shown great potential for the accurate determination of particle size distributions. The well-established LUMiSizer(R) is customized by a new design allowing for higher rotor speeds, improved thermal insulation, and measurement cell assembly. The latter enables sedimentation analysis of nanoparticles (NPs) in sector-shaped centerpieces. The measurement window of AC experiments is assessed by the Peclet (Pe) number. It is shown that at low Pe numbers (0.7 < Pe < 30), sedimentation, and diffusion can be accurately and simultaneously analyzed from the sedimentation boundaries within one experiment. Moreover, sedimentation properties can be reliably determined up to Pe numbers of 4000. The thermal characteristic throughout the sedimentation analysis is validated by measuring polystyrene particles at elevated temperatures. Moreover, the performance of the setup is demonstrated by determining the sedimentation properties of SiO2 NPs at intermediate Pe numbers in excellent agreement with results from analytical ultracentrifugation experiments. Finally, for the first time, an accurate analysis of the core–shell properties of Au NPs via AC is presented. By combining the analysis of sedimentation and diffusional properties at low Pe numbers, the shell thickness of the stabilizer cetyltrimethylammonium bromide alongside the core diameter distribution of the Au NPs is determined.
CRIS-Team Scopus Importer:2020-06-19
Keywords: analytical centrifugation; core–shell nanoparticles; layering effects; nanoparticle characterization; sedimentation analysis

Progress in Multidimensional Particle Characterization - Frank, Uwe; Uttinger, Maximilian; Wawra, Simon; Lübbert, Christian; Peukert, Wolfgang (KONA Powder and Particle Journal, 2021)
The properties of particle ensembles are defined by a complex multidimensional parameter space, namely particle size, shape, surface, structure, composition and their distributions. Macroscopic product properties are a direct result of these disperse particle properties. Therefore, the comprehensive multidimensional characterization of particle ensembles is a key task in any product design. However, the determination of complex property distributions is major challenge. We provide a broad overview of the current tools for multidimensional particle characterization. First, the mathematical handling of multidimensional (nD) property distribution is outlined as a necessary framework for the correct handling of nD particle size distributions (PSDs). Then, well-established techniques as well as recent developments with the potential to extract nD property distributions are reviewed. Exsitu imaging techniques like electron tomography or Raman spectroscopy with AFM co-localization, for instance, provide a resolution on the level of single particles but are limited in terms of sample statistics. A particular focus lies therefore on methods in the gas and the liquid phase, which provide multidimensional particle properties either directly or by a combination of one-dimensional technique

Structural factors controlling size reduction of graphene oxide in liquid processing - Nacken, Thomas; Halbig, Christian E.; Wawra, Simon; Damm, Cornelia; Romeis, Stefan; Walter, Johannes; Tehrani, Mohammad J.; Hu, Yichen; Ishii, Yoshitaka; Eigler, Siegfried; Peukert, Wolfgang (Carbon, 2017)
Graphene oxide materials can be prepared in manifold synthesis approaches and allow for further post-functionalization to adopt the properties of the desired application. Small sized sheets with lateral dimensions on the 100 nm scale are e.g. beneficial for cell applications. Breakage of sheets by liquid phase processing is an ideal way to generate such nano-sized sheets. However, until now it is unknown how functionalization influences the breakage behavior. We have chosen single layered oxo-functionalized graphene (oxo-G) derivatives with lattice defects < 1% to evaluate their size reduction rate upon ultrasonication of flakes with respect to the type and degree of functionalization of the graphene sheets. Lateral dimensions of the processed sheets were quantitatively determined in solution by analytical ultracentrifugation. The highest size reduction rate is observed for pristine oxo-G, which bears the highest degree of functionalization of around 60% and the negatively charged organosulfate group. Partial hydrolysis of organosulfate, or conversion of surface-functional groups to hydroxyl-groups in majority or partial defunctionalization lead to size-reduction rates which are up to 25% lower in comparison with the initial oxo-G. Moreover, the size reduction rate can be correlated in first approximation also with UV–vis spectroscopy.

The Stokes–Einstein–Sutherland Equation at the Nanoscale Revisited - Baer, Andreas; Wawra, Simon; Bielmeier, Kristina; Uttinger, Maximilian; Smith, David M.; Peukert, Wolfgang; Walter, Johannes; Smith, Alexander Kingsbury (Small, 2023)
The Stokes–Einstein–Sutherland (SES) equation is at the foundation of statistical physics, relating a particle's diffusion coefficient and size with the fluid viscosity, temperature, and the boundary condition for the particle-solvent interface. It is assumed that it relies on the separation of scales between the particle and the solvent, hence it is expected to break down for diffusive transport on the molecular scale. This assumption is however challenged by a number of experimental studies showing a remarkably small, if any, violation, while simulations systematically report the opposite. To understand these discrepancies, analytical ultracentrifugation experiments are combined with molecular simulations, both performed at unprecedented accuracies, to study the transport of buckminsterfullerene C60 in toluene at infinite dilution. This system is demonstrated to clearly violate the conditions of slow momentum relaxation. Yet, through a linear response to a constant force, the SES equation can be recovered in the long time limit with no more than 4% uncertainty both in experiments and in simulations. This nonetheless requires partial slip on the particle interface, extracted consistently from all the data. These results, thus, resolve a long-standing discussion on the validity and limits of the SES equation at the molecular scale.
CRIS-Team Scopus Importer:2023-10-20
Keywords: analytical ultracentrifugation; boundary condition; Green–Kubo formalism; molecular dynamics; Stokes–Einstein–Sutherland equation